Порфмий - греческий город у переправы через Киммерийский Боспор - Вахтина, М.Ю. (Кримське відділення Інституту сходознавства ім. А.Ю. Кримського НАН України, 2009)
Боспорский город Порфмий традиционно отождествляют с руинами античного городища, обнаруженными к северо-востоку от г. Керчи, на возвышенном плато недалеко от побережья Керченского пролива. Первые его раскопки были проведены Боспорской архе-ологической экспедицией ЛОИА АН СССР/ИИМК РАН в 1953 г. За несколько десятилетий систематических раскопок был накоплен значительный археологический материал, позволяющий приблизиться к пониманию особенностей жизни и своеобразия материальной культуры этого «малого» боспорского города. Боспорське місто Порфмій традиційно ототожнюється з руїнами античного городища, виявленого до північного сходу від м. Керч, на підвищеному плато неподалік від узбережжя Керченської затоки. Перші його розкопки були проведені Боспорською археологічною експедицією ЛОІА АН СРСР/ІІМК РАН у 1953 р. За декілька десятиріч систематичних розкопок був накопичений значний археологічний матеріал, який дозволяє наблизитися до розуміння особливостей життя та своєрідності матеріальної культури цього «маленького» боспорського міста. The article summarizes the main achievements in the investigation of the Greek Bosporan city of Porthmion. Traditionally, Porthmion is identified with the remains of ancient town situated north-east of the modern city of Kerch on the outskirts of the village Zhukovka. Information about a settlement called Porthmion is provided by ancient authors. That the name is derived from the Greek πορθμόζ (crossing) is fairly obvious and has never been questioned. Indeed, both written and archaeological sources suggest that one of the traditional routes arcoss the Strait of Kerch linking the Kuban region with the Crimea ran close to the city. The proximity of Porthmion to the routs connected European and Asiatic parts of Bosporos Kingdom, which have been also used by nomad tribes with no doubt reflected at the history of the Greek settlement.